2017
DOI: 10.1002/chem.201700021
|View full text |Cite
|
Sign up to set email alerts
|

Bistability in Organic Magnetic Materials: A Comparative Study of the Key Differences between Hysteretic and Non‐hysteretic Spin Transitions in Dithiazolyl Radicals

Abstract: Dithiazolyl (DTA)-based radicals have furnished many examples of organic spin-transition materials, some of them occurring with hysteresis and some others without. Herein, we present a combined computational and experimental study aimed at deciphering the factors controlling the existence or absence of hysteresis by comparing the phase transitions of 4-cyanobenzo-1,3,2-dithiazolyl and 1,3,5-trithia-2,4,6-triazapentalenyl radicals, which are prototypical examples of non-bistable and bistable spin transitions, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 52 publications
(120 reference statements)
4
38
0
Order By: Relevance
“…Thermal fluctuations at room temperature thus transform the dimerized columns of the minimum energy configuration of 1--HT into regular columns. A close inspection into the AIMD trajectories reveal that this transformation is achieved by means of the so--called pair--exchange dynamics (PED) mechanism, previously detected in the HT polymorphs of TTTA 65 and 4--NCBDTA 66 . When this mechanism is operative, each radical continually exchanges the adjacent neighbor (upper or lower) with which it forms a dimer.…”
Section: Dynamics Of the Ht Polymorphs Of Pdta And Tdpdtamentioning
confidence: 71%
See 1 more Smart Citation
“…Thermal fluctuations at room temperature thus transform the dimerized columns of the minimum energy configuration of 1--HT into regular columns. A close inspection into the AIMD trajectories reveal that this transformation is achieved by means of the so--called pair--exchange dynamics (PED) mechanism, previously detected in the HT polymorphs of TTTA 65 and 4--NCBDTA 66 . When this mechanism is operative, each radical continually exchanges the adjacent neighbor (upper or lower) with which it forms a dimer.…”
Section: Dynamics Of the Ht Polymorphs Of Pdta And Tdpdtamentioning
confidence: 71%
“…Note that 1--LT--0 and 1--HT--0 radical. 65 The regular π--stacks of the HT phase of 4--NCBDTA were also found not to be a minimum energy structure at 0 K. 66 In contrast to the results obtained for 1--HT, the variable--cell optimization of 2--HT did not lead to any intra--stack dimerization process. Accordingly, the 2--HT--0 structure preserves the uniform π--stacking motif observed in the X--ray structure of 2--HT.…”
Section: Minimum Energy Configurations Of the Lt And Ht Polymorphs Of Pdta And Tdpdtamentioning
confidence: 88%
“…Over the past few decades, a number of stable organic radicals including nitronyl nitroxide(NN), oxoverdazyl (OVER), dithiadiazolyl (DTDA) have been successfully developed. [6][7][8][9] One of the other thermally robust monoradical is 1,2,3-benzotriazinyl (Blatter's) radical (shown in Fig. 1), which was first reported by Blatter and co-workers in 1968.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies on TTTA 16,25 and 4-NCBDTA 26 have already reported their magnetic topology and their corresponding simulated magnetic susceptibility curves. For both compounds, good agreement was accomplished with respect to the experimental data.…”
Section: Magnetic Susceptibility Curves: Calculated Vs Experimentalmentioning
confidence: 99%
“…For DTA-based materials, this flaw is due to the fact that a single geometry has been disclosed not to be representative enough of the system due to the thermal fluctuations that the crystal experiences. 26,28 Despite being aware of the fact that molecular dynamics studies are needed to address this issue (and will soon be performed), the static results provide a rationale for the different magnetic responses of the two phases of PDTA and TDPDTA. The resulting data are in agreement with previous studies on TTTA and 4-NCBDTA.…”
Section: Magnetic Susceptibility Curves: Calculated Vs Experimentalmentioning
confidence: 99%